Current Systems in Psychology - Amber Haque (International Institute of Islamic Thought, 2001)
This book is about systems in psychology. A system generally consists of theoretical propositions and their methodologies. Most systems of psychology, the author contends, have a theoretical orientation, but some do not have coherence and unity. As far as methodology is concerned, some systems use an eclectic approach, while others use a limited set of methods in their inquiry into human behavior and mental processes. The author defines a system as "an orderly and logical construction for dealing with data and theories of the subject in a unified and coherent manner; it uses a set of postulates (even if implicitly) and usually a single methodology" (p. 4). The book consists of eight parts with 14 chapters. Altogether, ten major and six additional systems are described in various chapters that are packed with not only historical perspectives but a thorough and critical analysis as well. Additionally, an evaluative summary of each system, its contributions to psychology and relationship with other systems, is also given. Part I covers an introduction to the systems, the historical background and the logic of science. After the introductory chapter, which is an overview of the whole book, chapter 2 presents a sketch of the older concepts in psychology, starting from the time of hunter-gatherers and herders to Hellenic Greeks. Together with the early and non-western civilizations (e.g., Mesopotamian, Egyptian, Chinese, and Indian), this chapter covers aspects of the Naturalistic Psychology of Socrates, Plato, and Aristotle. The author examines the origin of mind-body dualism during these stages of developments. It is pointed out that in the western world, the mind-body phenomenon first appeared in the first or second century BC in Alexandria when the study of nature was abandoned. Aristotle emphasized the interaction of organism and environment, rather than internal factors, as de- g forces for the individual. The term "psyche" was coined after this period, when the intellectuals and the Christian theologians turned inward, looking for explanations of human behavior, and this convention dominated throughout the middle ages. Although natural sciences freed themselves from theology, psychology remained bound to it until it got the attention of philosophy. The author says that the classical systems in psychology until early 1960s were primarily reactions to these age-old questions. He also briefly explains the concept of the "Logic of Science" while describing terms like mental constructs, its typtypes, criteria, the mindbody dualism, and reductionism ...